Designed formation of InVO4/CeVO4 hollow nanobelts with Z-scheme charge transfer: Synergistically boosting visible-light-driven photocatalytic degradation of tetracycline. Issue 6 (December 2020) - Ding, Weichen; Lin, Xian; Ma, Guohong; Lu, Qifang
Graphical abstract: The InVO4 /CeVO4 hollow nanobelts possess the excellent photocatalytic performance than the pristine InVO4 and CeVO4 nanobelts. The Z-scheme mechanism significantly inhibits the recombination of electron-hole pairs, thus improving the photocatalytic activity. Highlights: InVO4 /CeVO4 nanobelts possess excellent photocatalytic performances towards tetracycline. Due of the different diffusion rate of Ce and In, the hollow structure is formed. Calculated work functions verify the direction of electrons transfer. A possible Z-scheme reaction mechanism is evidenced by XPS and MS analysis. Abstract: As the potential candidates for photodegradating pharmaceutical pollutants, the highly efficient, stable and recyclable Z-scheme photocatalysts, that are superior to the widely studied heterojunction photocatalysts, are very fascinating yet challenging. Herein, hollow structured InVO4 /CeVO4 nanobelts with large heterogeneous interface and huge internal cavity are well-designed and prepared through an efficient electrospinning-calcination route. Owing to a large surface-to-bulk ratio, when used as visible-light photocatalytic materials for photochemical decomposition of the residual tetracycline (TC) aqueous solution, these InVO4 /CeVO4 hollow nanobelts with porous structure and nanocrystal subunits exhibit excellent photocatalytic activity and very high stability, compared with pristine CeVO4 and InVO4 nanobelts. A possible Z-scheme reaction mechanism for the enhanced photocatalytic performance is tentatively proposed by PL, active species trapping experiments, XPS and EPR analysis, as well as calculated work functions of different crystal faces. This work underlines the importance of heterojunction construction, and presents a feasible protocol for the rational design of active photocatalysts under solar light for the photodegradation of environmental pollutants or for environmental purification.